2019
DOI: 10.1111/jan.14171
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factors associated with depression in infertility patients

Abstract: Aims To clarify gender differences in the demographic variables and infertility problems associated with depression among men and women undergoing infertility treatment. Design A cross‐sectional study. Methods We surveyed 380 women and 360 men undergoing infertility treatment at the reproductive medicine center of a hospital in China's Ningxia Province from March ‐ September 2016. Results For women, ethnicity, the number of clinic visits, social concern, and sexual concern were factors linked with depression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 58 publications
(107 reference statements)
2
35
0
Order By: Relevance
“…Different countries were involved. Five studies were conducted in Iran, 18–22 four in Turkey, 23–26 three in Italy, 27–29 three in America, 30–32 three in Sweden, 33–35 two in India, 36 37 two in the Netherlands, 38 39 one in Finland, 9 two in Africa, 40 41 one in Saudi Arabia, 42 one in Japan, 43 two in China 44 45 one in Pakistan 46 and two in Greece. 47 48 The smallest sample size was 87, 47 and the largest was 98 320.…”
Section: Resultsmentioning
confidence: 99%
“…Different countries were involved. Five studies were conducted in Iran, 18–22 four in Turkey, 23–26 three in Italy, 27–29 three in America, 30–32 three in Sweden, 33–35 two in India, 36 37 two in the Netherlands, 38 39 one in Finland, 9 two in Africa, 40 41 one in Saudi Arabia, 42 one in Japan, 43 two in China 44 45 one in Pakistan 46 and two in Greece. 47 48 The smallest sample size was 87, 47 and the largest was 98 320.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that women with live births had an increased risk of certified depression compared with women with no live births. This is because it is probably more difficult to manage a postpartum depression condition, the construction of parental competence, and taking care of a child, rather than experiencing infertility, mourning, and the loss of not having a child [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in this study, the maternal and paternal antenatal attachment progressively and steadily increased from the first trimester of pregnancy until 3 months post-partum. Many studies confirmed that the attachment increases as the pregnancy progresses, regardless of the conception type [ 38 , 46 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in the Introduction, infertility and ART treatments represent critical and potentially stressful experiences, which can lead to individual and relational distress for both partners ( De Berardis et al, 2014 ; Koert and Daniluk, 2018 ). However, literature has highlighted gender differences in coping with these experiences and in their impact on individual and relational well-being ( Bayley et al, 2009 ; Davidovà and Pechovà, 2014 ; Ying et al, 2015 ; Bai et al, 2019 ). Given that several aspects could be the cause of these differences, the aim of the present study was to assess gender differences in couples undergoing medical treatment for conception, focusing on both partners’ individual and relational well-being as well as on psychological factors that could be considered as risk/protective factors for well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of infertility and ART has been well-documented in both women and men; in this direction, it is important to notice that important gender differences on individual and relational well-being have been reported (Bayley et al, 2009;Davidovà and Pechovà, 2014;Ying et al, 2015;Bai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%